Programmable DSP systems using FPGA - Tan, Eng Chong; Abdul Rahman, Abdul Wahab; K., K. Wong (1996)
The paper presents our experience oj using FPGA as a cost-efective and flexible tool in the prototyping and development of DSP applications or systems.